2014
DOI: 10.13005/ojc/300118
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Investigation of Dye-Sensitized Solar Cells Based on the Zinc Oxide Nanowires

Abstract: In this paper, we synthesized ZnO nanowires in dye sensitized solar cells. The nanowires have been fabricated using fast-microwave-hydrothermal process.We verify the effects of different lengths of ZnO nanowires on efficiency and absorptionofdye sensitized solar cells. J-V curves of the fabricated ZnO nanowire-based mercurochrome-sensitized solar cells indicated that the shortcircuit current density would increase with increasing the length of nanowires.We also fabricate more efficient N719-sensitized solar ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 23 publications
3
6
0
Order By: Relevance
“…In Table 1, even though it was observed that the film made with ZnO has the highest performance, ZnO/NiO composite nanoparticles can provide large surface areas for the dye adsorption. The photovoltaic performances of obtained DSSCs employing ZnO nanoparticles are comparable to published literature [29,30]. In addition, the sc and the cell efficiency of the solar cell constructed using NiO are in good agreement with the literature [31,32].…”
Section: Resultssupporting
confidence: 88%
“…In Table 1, even though it was observed that the film made with ZnO has the highest performance, ZnO/NiO composite nanoparticles can provide large surface areas for the dye adsorption. The photovoltaic performances of obtained DSSCs employing ZnO nanoparticles are comparable to published literature [29,30]. In addition, the sc and the cell efficiency of the solar cell constructed using NiO are in good agreement with the literature [31,32].…”
Section: Resultssupporting
confidence: 88%
“…As revealed in the figures, the photovoltaic performances of our DSSCs employing ZnO NRs are comparable to published literature [22,23,24]. A higher amount of dye was adsorbed on longer NRs than on shorter NRs, indicating that longer NRs improve photon absorption and carrier generation.…”
Section: Resultssupporting
confidence: 86%
“…Dye sensitized solar cells (DSSC) have attracted considerable attention in recent years as an alternative to conventional silicon solar cells [1][2][3][4][5][6][7][8] . Dye sensitized solar cell consist of photoelectrode, counterelectrode and electrolytes.…”
Section: Introductionmentioning
confidence: 99%